Prevalence and Risk Assessment of Salmonella Spp. in Sliced Fruit - Pui, Chai Fung (2011)
Fresh fruits and vegetables are increasingly recognized as a source of salmonellosis outbreaks in many parts of the world. Such products are always eaten raw or with minimal processing and if contaminated with Salmonella, they may represent a health hazard to the consumers. The public health importance of Salmonella in man led the present study to determine the prevalence and quantity of Salmonella spp., Salmonella Typhi and Salmonella Typhimurium in sliced fruits. In domestic kitchen, the food contact surfaces are sometimes improperly cleaned which ease the formation of biofilm by Salmonella. Subsequent detachment from the biofilm layer can be at risk for contamination of fresh fruits and vegetables. Hence, the quantification of biofilm formed by Salmonella Typhi and Salmonella Typhimurium on plastic cutting board used in domestic kitchen was determined in this study prior to analyzing the transfer rate of these two pathogens to the fruit model. The most probable number (MPN)-multiplex polymerase chain reaction (PCR) was used for the prevalence and quantification studies. A multiplex PCR was optimized for the simultaneous detection of Salmonella spp., Salmonella Typhi and Salmonella Typhimurium in sliced papaya, watermelon, mango, sapodilla, jackfruit, dragon fruit and honeydew. The prevalence of Salmonella spp., Salmonella Typhi and Salmonella Typhimurium in 210 samples of sliced fruits examined were 23.3%, 7.6% and 3.8%, respectively with estimated quantity varied from 0 to 19 MPN/g. On the other hand, the prevalence of Salmonella spp. discovered from the total sliced fruits of hawker stalls were three times higher than those from hypermarkets at 30% and 10% respectively at p<0.05. Salmonella spp. were detected in 23.3% fruit samples using MPN-multiplex PCR and at 9.5% using MPN-plating method. Out of the seven types of fruits examined, dragon fruit from hawker stalls showed the highest prevalence of contamination with 75% Salmonella spp., 40% Salmonella Typhi and 25% Salmonella Typhimurium. Hence, it was used as the fruit model to study the biofilm formation by Salmonella Typhi and Salmonella Typhimurium on plastic cutting board and their subsequent transfer to dragon fruit. By using crystal violet assay, it was found that biofilm formation of Salmonella Typhi and Salmonella Typhimurium on plastic cutting board was the highest at 12 h when they are incubated in physiological saline solution at 28°C. On the transfer of these two pathogens from plastic cutting board to dragon fruit, results showed their mean transfer percentages were 92.38 and 91.30%respectively for Salmonella Typhi and Salmonella Typhimurium. These highlighted that biofilm can cross-contaminate dragon fruit and contribute to cross-infection. As a conclusion, there is a need for the health authority to look into the risk assessment of sliced fruits in Malaysia. The risk of microbial transfer from food contact surface to fresh fruits should also be of concern to prevent foodborne disease outbreaks.